Juror Discussions About Evidence, 1997-1998: (Arizona) - Hannaford, Paula L. ([Verlag nicht ermittelbar], 1999)
These data were collected in conjunction with an evaluation of the Arizona court reform effective December 1, 1995, to permit jurors in civil cases to discuss the evidence prior to deliberations. The datasets consist of survey responses by judges, jurors, attorneys, and litigants in all civil cases conducted in Maricopa, Pima, Mohave, and Yavapai counties in Arizona between June 15, 1997, and January 31, 1998. Civil cases in the participating courts were randomly assigned to one of two experimental conditions: (1) jurors were told they could discuss the evidence prior to deliberation according to Rule 39(f) of the Arizona Rules of Civil Procedure, or (2) jurors were told they could not discuss the evidence per the previous admonition. The datasets contain survey responses under both conditions. Part 1, Case Characteristics Data, contains information from two questionnaires completed by judges about the lawsuit, the parties, the trial procedures, and the case outcome. The data in Part 2, Juror Questionnaire Data, cover jurors' views regarding the complexity of the case, the importance of witnesses and testimonies, and attorneys' performances. The variables in Part 3, Attorney Questionnaire Data, offer information on attorneys' opinions of the jurors, the opposing counsel, and the verdict. Part 4, Litigant Questionniare Data, consists of litigants' views regarding the jurors and the verdict. Demographic data include respondents' gender, age, race, income, and job status.